Suco de açaí funcional: estabilidade, processamento, digestão e fermentação pela microbiota intestinal humana - Reges, Bianca Mara (2024)
The present study is divided into two stages. The first stage addresses the preparation of açaí juice containing gluco-oligosaccharides and dextran processed by high-intensity ultrasound. In the second stage, the stability of açaí juice containing gluco-oligosaccharides and dextran fermented with Bifidobacterium breve NRRL B-41408, stored for 42 days at 4°C, was evaluated. The prebiotic and synbiotic juices were subjected to in vitro simulated digestion and evaluated for their impact on human gut microbiota. The non-sonicated prebiotic juice contained glucose (16.55 g/L), fructose (27.59 g/L), gluco-oligosaccharides (82.56 g/L), and dextran (23.30 g/L). After processing, the gluco-oligosaccharides and dextran in the sonicated prebiotic juice (373 W/cm²; 9 min; 25°C) had concentrations of 77.82 and 23.12 g/L, respectively, and resisted in vitro simulated digestion, promoting an increase in short chain fatty acids (SCFAs), mainly propionic acid. The sonicated juice increased the relative abundance of the Rikenellaceae and Acidaminococcaceae families after fecal fermentation, as well as improved the richness and diversity of the microbiota evaluated. In the synbiotic açaí juice, the viable cell count of B. breve was 9.0 log CFU/mL after fermentation and during refrigerated storage (42 days), indicating that B. breve maintained its metabolism at low temperatures and under acidic conditions. The gluco-oligosaccharides and dextran in the synbiotic juice exhibited resistance to in vitro simulated digestion and promoted the production of SCFAs, mainly acetic, propionic, and isobutyric acids. The synbiotic açaí juice improved species diversity and reduced the abundance of species associated with irritable bowel syndrome and intestinal microbiota imbalance. Both açaí juices produced may contribute to improving the host's overall health by increasing beneficial bacteria, balancing the intestinal microbiota, and producing metabolites such as SCFAs. Additionally, the developed juices can be considered functional foods and suitable non-dairy carriers for B. breve, gluco-oligosaccharides and dextran.